CHANGING COUNSELING COMMUNICATION PATTERNS: FROM FACE-TO-FACE TO DIGITAL PLATFORMS - Obianto, Agung (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Digital transformation in counseling services at the Darussalam Blokagung Islamic Boarding School was analyzed through a qualitative study with a case study approach, exploring the dynamics of shifting communication patterns from face-to-face to digital platforms after the acceleration of technology adoption during the COVID-19 pandemic. The study aims to identify changes in communication dynamics, evaluate the effectiveness of digital platforms, and analyze adaptation challenges, with data collection methods through observation, in-depth interviews, FGD, and document analysis. The results show three key findings: (1) 40% of educators experience technical unpreparedness due to lack of training and infrastructure, (2) 30% of the community rejects change because it is considered contrary to traditional values ??of direct interaction, and (3) 30% variation in students' academic outcomes related to the gap in access to digital devices. The study concludes the need for a hybrid model that integrates technological advantages with face-to-face interactions, taking into account infrastructure factors, digital literacy, and the socio-cultural context of Islamic boarding schools. These findings provide a conceptual framework for the development of adaptive counseling services in Islamic boarding school-based educational environments.